INTERCULTURAL ASPECTS IN LANGUAGE EDUCATION - Titi Rokhayati (Universitas Muria Kudus, 2018)
Intercultural understanding essentiallybecomes a part of living with others in the diverse world of the twenty-first century. It assists people to become responsible local and global citizens through their education for living and working together in an interconnected world. Language is a major component and supporter of culture as well as a primary tool for transferring message, which is inextricably bound with culture. Language is a key component of culture. It is also a primary medium for transmitting the culture itself. Without language, culture would not be possible. Students learning their native language are learning their own culture. Meanwhile, learning a second language also involves learning a second culture to varying degrees. A language is influenced and shaped by culture. It reflects culture. Cultural differences are the most serious areas causing misunderstanding, unpleasantness and even conflict in cross-cultural communication. Both foreign language learners and teachers accordingly should pay more attention to cultural communication information.